Fabrication and appraisal of axitinib loaded PEGylated spanlastics against MCF- 7 and OV- 2774 cell lines using molecular docking methods and in-vitro study. - Randa Mohammed Zaki; Basmah Nasser Aldosari; Layla A Alkharashi; Alyaa Alsalhi; Obaid Afzal; Bodoor Ghanem Alanazi; Maha Alsunbul; Rawan Bafail; Fatma I Abo El-Ela; Hanan O Farouk (PLoS ONE, 2025)
Axitinib is a second-generation tyrosine kinase inhibitor that works by selectively inhibiting vascular endothelial growth factor receptors (VEGFR-1, VEGFR-2, VEGFR-3). Through this mechanism of action, axitinib blocks angiogenesis, tumor growth and metastases and therefor it shows significant promise as a chemotherapeutic agent for various types of cancer. Nevertheless, the clinical efficacy of this substance is hindered by its restricted solubility in water and inadequate stability. To address these challenges, we developed spanlastics with polyethylene glycol (PEG) to improve the efficacy and stability of axitinib against breast and ovarian tumor malignancies in a targeted manner. Moreover, the study conducts a thorough examination of the interactions between the ligand Axitinib alone or after coating with PEG and a diverse array of protein types in breast (Dopamine, VEGFR) and ovarian cancer (EGFR, BCL-xL). The fabrication of axitinib- spanlastics was achieved through a thin-film hydration method. The evaluation of the impact of formulation factors on the features of nanovesicles was conducted using the I- optimal design. Subsequently, the optimum formulation was calculated. The optimal formulation was coated with polyethylene glycol (axitinib-PEG-spanlastics). An in vitro assessment was computed to evaluate the efficiency of the optimized axitinib-PEG-spanlastics against the MCF-7 breast cancer cell line and the OV-2774 ovarian cancer cell line. The optimized axitinib-PEG-spanlastics formulation exhibited a diameter of 563.42 ± 8.63 nm, accompanied by a zeta potential of -46.44 ± 0.09 mV. The formulation demonstrated an 84.32 ± 3.64% entrapment percent and a cumulative release of 73.58 ± 3.37% during a 4-hour period. The results obtained from the WST-1 assay showed a significant decrease in the percentage of cell survival, reaching 50% at a concentration of 0.68 µM for the PEG-spanlastics. In contrast, the axitinib free drug suspension exhibited 50% cell survival at a concentration of 1.1 µM in the breast cancer (MCF-7) cell line. In MCF-7 cells, the percentage of apoptotic cells generated by axitinib-PEG-spanlastics compared to the free drug suspension was 70.76 ± 4.971% vs. 32.6 ± 1.803%, while in OV-2774 cells, it was 43.55 ± 4.243% vs. 24.44 ± 4.950%. These results propose that Axitinib-PEG-spanlastics have the potential to be a successful nanoplatform for targeting breast and ovarian cancer and effectively managing tumors.